The Efficacy of Upper Extremity Neuroma Surgery in Reducing Long-Term Opioid Use in Patients with Preoperative Opioid Use - Emovon III, Emmanuel O.; Langdell, Hannah; Rebello, Elliott; Albright, J. Alex; Ong, Ethan; Joh, Daniel Y.; Mithani, Suhail K.; Li, Neill Y. (Journal of Reconstructive Microsurgery, 2025)
Neuromas can cause severe neuropathic pain, leading to functional decline and psychosocial distress. For pain relief, patients refractory to medications for neuropathic pain may be prescribed opioids; however, such use has been shown to have unfortunate adverse effects. With increasing awareness and diagnostic capabilities for neuroma formation, this study evaluates whether upper extremity neuroma excision may reduce opioid use and if adjunctive nerve procedures further reduce opioid use.The PearlDiver database was queried for patients undergoing upper extremity neuroma excision surgery from 2010 to 2020. Patients with opioid prescription fill records preoperatively were extracted and stratified by an operative technique involving either (1) excision alone, (2) nerve implantation into bone or muscle, or (3) nerve reconstruction. Records were then assessed at 1, 3, and 6 months postoperatively to assess for opioid use. Prescription fill rates at 1, 3, and 6 months postoperatively were then assessed across techniques.Of the 14,330 patients that underwent upper extremity neuroma excision, 4,156 filled opioids preoperatively. Excision led to significant reductions in opioid prescription fill rates postoperatively, decreasing to 67.4% at 1 month and to 57.5% by 6 months (p < 0.001). Excision alone resulted in lower opioid use compared with excision with implantation at all postoperative time points (p < 0.05). At 6 months, opioid use was also significantly less following excision with nerve reconstruction compared with implantation (56.4% vs. 65.6%, p = 0.0096). There were no differences between excision alone and excision with nerve reconstruction.Neuroma excision significantly reduces opioid use in patients with preoperative opioid use while adjunctive operative techniques did not potentiate opioid reduction. This highlights the importance of understanding patient complaints, neuroma localization, and candidacy for excision as an effective measure for addressing opioid use in patients with preoperative opioid dependence.
Keywords: neuroma; opioids; neuroma surgery; nerve surgery